Reconstructing depth from spatiotemporal curves - Rodrigues, Rui (2002)
We present a novel approach for 3D reconstruction based on multiple video frames taken from a static scene. Our solution emerges from the spatiotemporal analysis of video frames. The method is based on a best fitting scheme for spatiotemporal depth curves, which allows us to compute 3D world coordinates of the objects within the scene. As opposed to a large number of current methods, our technique deals with random camera movements in a transparent way, and even performs better in these cases than with pure translation. Robustness against occlusion and aliasing is inherent to the method as well.